2010
DOI: 10.4028/www.scientific.net/amm.24-25.147
|View full text |Cite
|
Sign up to set email alerts
|

Digital Holographic Interferometry by Using Long Wave Infrared Radiation (CO<sub>2</sub> Laser)

Abstract: We show how digital holographic interferometry in the Long Wave InfraRed spectral range (LWIR) can be used for the investigation of mechanical structures. The 10.6 μm radiation is produced by a CO2 Laser. Experimental results showing that the method can be used to locate defects in a panel are presented and advantages and disadvantages of this approach are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…В настоящее время СО 2 -лазеры с успехом приме-няются как для диагностики плазмы [3,4], так и для интерферометрического контроля формы и деформации разнообразных объектов, таких как крупногабаритные зеркала [5], строительные сооружения [6], произведения искусства [7]. В последнем случае интерферограмма, фиксирующая скрытые дефекты произведения живопи-си, сохраненная на электронном носителе, выполняет функцию индивидуальной " идентификационной метки", снижающей вероятность подмены подлинника картины копией.…”
Section: Introductionunclassified
“…В настоящее время СО 2 -лазеры с успехом приме-няются как для диагностики плазмы [3,4], так и для интерферометрического контроля формы и деформации разнообразных объектов, таких как крупногабаритные зеркала [5], строительные сооружения [6], произведения искусства [7]. В последнем случае интерферограмма, фиксирующая скрытые дефекты произведения живопи-си, сохраненная на электронном носителе, выполняет функцию индивидуальной " идентификационной метки", снижающей вероятность подмены подлинника картины копией.…”
Section: Introductionunclassified
“…The development of the set-up we use was already presented in several papers: we studied various configurations such as LWIR DHI [17] [18] , ESPI [18] and shearography [18] . The camera is a Jenoptik Variocam HR based on an uncooled microbolometer array with 640x480 pixels, each pixel being 25 µm wide.…”
Section: Set-upmentioning
confidence: 99%
“…Our first step in this project was to assess the roughness of these samples, and we showed that most of the above cited materials have a roughness that is high enough to generate speckle with CO 2 lasers [23]. Preliminary DHI experiments were already reported with these samples [24].…”
Section: Introductionmentioning
confidence: 99%